The Development of Cultural Hybridization in Chinese Professional Football Clubs and Problems of Cultural Hybridization Between Chinese Local and Western Football Players - Yanying Chen; Nor Eeza Zainal Abidin; Mohd Salleh Aman (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The Director of the Ministry of Physical Education and Sports contended that the integration of Western football players could enhance the overall quality of competition in the Chinese Football Association Super League. This initiative reflects the ongoing globalisation of Western football culture in China. The Director emphasised the necessity of providing social and cultural support for Western football players and fostering their engagement in a culturally inclusive environment within China. A document analysis methodology was employed to examine the evolving policies regarding the introduction of Western football players in China. Additionally, participant observation was utilised to investigate challenges arising from cultural hybridisation between Chinese and Western football players within Chinese football clubs. These challenges include issues related to intercultural communication, the alienation of expatriate players within local Chinese society, limited understanding among Chinese players regarding secondary attacks, and difficulties in collaborative play with Western strikers. The findings underscore the need for further research into strategies to enhance the cross-cultural competence of Chinese football players and address the challenges associated with cultural hybridisation in Chinese football clubs.